The Influence of Public Service Motivation on The Performance of Nurses at The Syekh Yusuf Hospital, Gowa Regency - Sriyani Windarti; Dian Ekawaty; Nurmulia Wunaini N; Mangindara; Fadillah Al-Afiana (Miracle Journal of Public Health, 2023)
Public service in Indonesia are still in the poor category. This is due to one of them because of the motivation of public service that have not been optimally embedded in the government apparatus so that in Indonesia the public services provided tend to be oriented only to fulfill the rules or personal interests without thinking about the welfare of the community. Based on the initial data obtained, it shows that from 2019-2021 there are still many medical record files collected that are not timely and incomplete. This shows that the performance of HR in inpatients is still not optimal. This study aims to determine the effect of public service motivation on the performance of nurses. The type of research used is quantitative research with a cross-sectional study approach. The population is 297 nurses. The sample in this study is 170 nurses. The sampling technique used in this study is non-probability sampling using a purposive sampling method. The tests used were chi-square analyzed using SPSS. The results of the Chi-Square analyzed in this study showed that of the four variables studied, there was only one variable that had an influence on the nurse’s performance, namely the self-sacrifice variable with p-value = 0.006 < 0.05. So it can be concluded that of the four variables studied, only one influential variable is the self-sacrifice variable.